Impacto do tempo de tratamento hemodialítico sobre a qualidade de vida em portadores de insuficiência renal crônica teminal - Santos, Paulo Roberto (2004)
Introduction: End-stage renal disease (ESRD) and hemodialysis (HD) are highlighted, among chronic diseases and therapies, as the ones that endanger more the health-related quality of life (HRQL). The impossibility of kidney transplantation for a portion of patients with ESRD make these patients undergo HD for a long period of time. Objectives: Compare the scores of HRQL of patients with ESRD according to the time in HD and verify the existence of correlation between HRQL and sociodemographic, clinic and laboratory factors. Methodology: Sample was constituted of 107 patients in HD at the Santa Casa’s Unit of Nephrology in Sobral, Ceará, Brazil, divided in three groups according to the time in HD. Group I included patients undergoing HD from 3 to 15 months; group II, patients undergoing HD from 16 to 60 months; and group II, patients in HD for over 60 months. Sociodemographic and clinical-laboratory data were collected, and the Medicai Outcomes Study Questionaire 36-Item Short Form Health Survey (SF-36) was used to measure HRQL. The SF-36 yields 8-scale profile: physical functioning (PF), role-physical (RP), bodily pain (BP), general health (GH), vitality (VT), social functioning (SF), role-emotional (RE), mental health (MH). Results: The average scores reached by groups I, II and III were, respectively: PF - 60,8 vs. 51,0 vs. 49,5 (p=0,196); RP - 32,5 vs. 27,3 vs. 41,6 (p=0,411); BP - 52,1 vs. 54,1 vs. 58,9 (p—0,539); GH - 43,6 vs. 39,6 vs. 38,3; VT - 48,9 vs. 47,5 vs. 54,1 (p=0,464); SF - 62,6 vs. 58,0 vs. 66,0 (p=0,501); RE - 31,2 vs. 31,6 vs. 43,2 (p=0,353) and MH - 63,2 vs. 56,0 vs. 69,4 (p=0,038). There was a statistic difference in the PF scores according to the comparison between 0 to 4 years of schooling vs. more than 4 years and between hypertensive nephrosclerosis as primary renal disease vs. glomerulonephritis, respectively: 47,5 vs. 64,5 (p=0,002) and 46,4 vs. 24,9 (p=0,049). The age presented linear and negative correlation with PF (r=-0,289, p=0,003), RP (r=-0,224, p=0,020), BP (r=-0,252, p=0,008), GH (r=-0,245, p=0,011), VT (r=-0,334, p<0,001) and SF (r=-0,270, p=0,05). There was a linear and positive correlation of the serum hemoglobin with BP (r=0,229, p=0,018) and VT (r=0,197, p=0,043), and the serum albumin with BP (r=0,200, p=0,039), GH (r=0,238, p=0,011) and VT (r=0,199, p=0,040). Conclusions: The group undergoing a long period of time in HD presented the higher score due to dimension MH, probably due to the patients’ psychological adaptation to the disease and the therapy. There was correlation between HRQL and years of schooling, primary renal disease, age, serum hemoglobin and serum albumin. The worst score referent to PF reveals the necessity of a physical rehabilitation strategy for the patients from the sample. The implementation of a regular exercise program in the Unit is suggested.